2008
DOI: 10.1002/jor.20606
|View full text |Cite
|
Sign up to set email alerts
|

ASARM‐truncated MEPE and AC‐100 enhance osteogenesis by promoting osteoprogenitor adhesion

Abstract: Matrix extracellular phosphoglycoprotein (MEPE) is a member of the SIBLING (Small Integrin-Binding Ligand, N-linked Glycoprotein) family of secreted glycophosphoproteins. Several previous studies have demonstrated that MEPE and its peptide motif, AC-100, may regulate bone mass and influence osteoblast activity, suggesting its potential for inclusion in novel therapeutic strategies aimed at increasing osteogenesis. Our study uses in vitro approaches to assess how adhesion of nonadherent cells is influenced by M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…It is reported that the C-terminal product ASARM peptide was able to inhibit mineralization processes in vitro and promote cell adhesion through the arginine-glycine-aspartate (RGD) sequence (8). MEPE with the ASARM peptide deleted promoted bone formation in culture and in mice (19), whereas N-terminal cleavage product from MEPE with RGD motif accelerated mineralization (8). Like other SIBLING proteins such as OPN, DMP-1, and DSP, post-translational modification of MEPE is believed to alter its effects on mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the C-terminal product ASARM peptide was able to inhibit mineralization processes in vitro and promote cell adhesion through the arginine-glycine-aspartate (RGD) sequence (8). MEPE with the ASARM peptide deleted promoted bone formation in culture and in mice (19), whereas N-terminal cleavage product from MEPE with RGD motif accelerated mineralization (8). Like other SIBLING proteins such as OPN, DMP-1, and DSP, post-translational modification of MEPE is believed to alter its effects on mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that recently MEPE with the ASARM peptide deleted was found to promote bone formation in culture and in mice [14]; similarly, a midterminal fragment of MEPE has been found to enhance cell binding [15] and pulp repair [16]. Thus, distinct components of MEPE appear to have different effects on mineralized tissue formation and signaling processes.…”
Section: Discussionmentioning
confidence: 99%
“…This is not the only evidence for a role for MEPE in the promotion of mineralisation. Recently, it has been shown that a truncated form of MEPE, which has the ASARM peptide removed, can promote bone mineralisation in culture and in mice (Sprowson et al 2008). Furthermore, a mid-terminal fragment of MEPE (termed 'AC100') has been shown to enhance cell binding, through the stimulation of focal adhesion kinase and ERK (Hayashibara et al 2004).…”
Section: Matrix Extracellular Phosphoglycoproteinmentioning
confidence: 99%